Concerning perceived and clinically-measured levels of halitosis. (1st January 2023) - Oshiro, Akiko; Zaitsu, Takashi; Inoue, Yuko; Srinarupat, Jarassri; Nguyen, Vy Thi Nhat; Nagai, Masato; Aida, Jun
Abstract: The different types of self-reported halitosis complaints include those where one feels that one's breath smells bad, where one feels that one has bad breath because of the attitudes of others, and where others have pointed out the presence of bad breath. The results of previous studies comparing the objective and subjectives measures of halitosis are inconsistent, and few studies have used gas chromatography (GC) to measure halitosis in a large sample. This study aimed to examine the objectively measured halitosis levels based on the reasons individuals are concerned about halitosis. We included 2063 patients who visited the halitosis clinic at a university dental hospital. Halitosis was assessed using GC, self-administered questionnaires, and oral examinations. Levels of volatile sulphur compounds (VSCs; H2 S, CH3 SH, and (CH3 )2 S) were set as objective measures of halitosis. Patients were grouped based on their answers to 'What made you concerned about bad breath?' into groups: 'self-perceived, ' 'attitudes of others, ' 'told by others, ' and other reasons. Univariate and multivariable linear regression analyses were performed to examine factors associated with VSCs and objective halitosis levels. Age, sex, oral health status, smoking, drinking, and breakfast habits were used as confounders. Patients who answered 'told by others' ( n = 691, 33.5%) showed the highest VSCs. Individuals whose halitosis was pointed out by others had higher objectively measured halitosis levels, while those concerned about the attitudes of others or perceived their own halitosis had lower objectively measured halitosis levels. These results suggest that the objective level of halitosis can differ on the basis of the reason underlying an individual's concern about their bad breath. Categorizing halitosis complaints and comparing them with objective halitosis levels may help reduce the anxiety of those who are concerned about halitosis and confirm the need for intervention for those with objective halitosis.